Bentuk dan Bahan Nisan Berinskripsi di Jawa dan Sumatera pada Abad ke-16 M - Awwalun K. R., Dimas Permadi; Ramadani, Exlima; Farizkha, Ivan Agusta (Local History & Heritage, 2024)
This study explores the patterns of shapes and materials used in inscribed gravestones in Java and Sumatra during the 16th century. These gravestones function as cultural artifacts, reflecting the social, religious, and aesthetic dimensions of the societies of that era. Utilizing historical and archaeological methods, the research examines data from Islamic burial sites in both regions. The findings reveal diverse patterns, including geometric, floral, and Arabic calligraphic designs, which were shaped by local traditions and cross-cultural interactions within the Islamic world. The materials used, such as andesite, marble, and limestone, indicate the utilization of local resources and reflect the social status of the deceased. This study contributes to understanding the cultural and aesthetic dynamics of 16th-century Javanese and Sumatran societies, while also demonstrating the significant influence of Islam on local art and architecture.